Posterior separation plasty for large incisional ventral hernias - N. K. Tarasova; A. V. Tarabukin; L. A. Temezhnikova; D. V. Mizgirev (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to evaluate the results of posterior separation plasty in patients with large incisional ventral hernias.METHODS AND MATERIALS. Results of surgical treatment of 19 patients with large incisional ventral hernias were analyzed, posterior separation plasty with a polypropylene mesh implant was done in all cases. Mean age of the patients was (57.8±2.8) years. Assessment of quality of life of patients was carried out (15.7±1.6) months after the operation using the SF-36 questionnaire, and the anterior abdominal wall and the area of surgical intervention were also examined.RESULTS. All patients of the study group had comorbidity, the most frequent were diseases of the cardiovascular system – in 14 (73.7 %) patients, pathology of the digestive tract – in 12 (63.2 %) patients, obesity – in 10 (52.7 %) patients. The mean duration of hernia presentation was (44.2±11.3) months. The average width of the hernial defect was (15.2±0.5) cm. Posterior separation plasty by A. M. Carbonell was used in 12 (63.2 %) patients, TAR-plasty – in 7 (36.8 %) patients. Mean hospital stay was (18.7±1.9) days. Postoperative wound complications developed in 5 (26.3 %) patients. Complications like abdominal compartment syndrome, pulmonary embolism, and deaths have not been noticed. Quality of life assessment (15.7±1.6) months after surgery revealed that the physical health (PH) was (48.35±2.63), and the mental health (MH) was 52.42±3.04. In addition, there were 3 (15.8 %) recurrences of hernia after posterior separation plasty by A. M. Carbonell method.CONCLUSION. The use of posterior separation plasty with mesh prosthesis made it possible to perform reconstruction of the anterior abdominal wall, avoiding the development of intra-abdominal hypertension and death. It is recommended to avoid the posterior separation plasty by A. M. Carbonell method because of the risk of recurrence of incisional ventral hernias, TAR-plasty should be preferred for use.